2019
DOI: 10.1113/jp277831
|View full text |Cite
|
Sign up to set email alerts
|

Ketone ester supplementation blunts overreaching symptoms during endurance training overload

Abstract: Key points Overload training is required for sustained performance gain in athletes (functional overreaching). However, excess overload may result in a catabolic state which causes performance decrements for weeks (non‐functional overreaching) up to months (overtraining). Blood ketone bodies can attenuate training‐ or fasting‐induced catabolic events. Therefore, we investigated whether increasing blood ketone levels by oral ketone ester (KE) intake can protect against endurance training‐induced overreaching. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
127
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(136 citation statements)
references
References 94 publications
(171 reference statements)
8
127
1
Order By: Relevance
“…In the study by Poffé et al (2019), there was no decrement in 30 min time trial performance, and 90 s sprint cycling performance was impaired to the same magnitude in both the KE and control group in response to the overload-training period, which returned to a value no different from pre-training after 3 days of recovery. From this standpoint, it could be suggested that both the KE and control group became FOR.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…In the study by Poffé et al (2019), there was no decrement in 30 min time trial performance, and 90 s sprint cycling performance was impaired to the same magnitude in both the KE and control group in response to the overload-training period, which returned to a value no different from pre-training after 3 days of recovery. From this standpoint, it could be suggested that both the KE and control group became FOR.…”
mentioning
confidence: 79%
“…Poffé et al . () make elaborate remarks throughout their paper to suggest that ketone ester intake is a potent nutritional strategy that is effective in preventing the development of non‐functional overreaching (NFOR) and in preventing symptoms of overtraining. However, they make no attempt at any point in their paper to individually classify the subjects as being overreached (either functional or non‐functional) or overtrained based on their change in cycling performance and resultant recovery timeline, a classification that is typically employed in human studies (Halson et al .…”
mentioning
confidence: 99%
“…In our recent article (Poffé et al . ) published in this journal, we demonstrated that ketone ester (KE) intake during a 3‐week endurance training overload period blunts the development of overreaching symptoms as well as enhances endurance exercise performance. The criticisms by Korevaar et al .…”
mentioning
confidence: 92%
“…As fellow scientists and endurance athletes, we read with interest the recent paper by Poffé and colleagues on ketone ester supplementation in endurance training (Poffé et al . ). The authors conclude that they demonstrated “that an oral ketone ester is a potent nutritional strategy that prevents the development of physiological overtraining symptoms and non‐functional overreaching”.…”
mentioning
confidence: 97%